The effect of compensation and work motivation on job Satisfaction employees of the Population and Civil Registration Office Kerinci Regency - Sumiati Sumiati; Ani Marlina; Desmawati Desmawati (Jurnal Mantik, 2023)
Human resources are a central factor in an organization, human resources are someone ready, willing, and able to contribute to efforts to achieve organizational goals. This study aims to determine the effect of compensation and work motivation on the job satisfaction of employees in the Population and Civil Registration Office Kerinci Regency. The respondents in this study were 31 employees. The analytical tools used for data processing are multiple linear regression analysis, multiple coefficients of determination and hypothesis testing with t-test and F-test. Based on the results of the analysis, show that compensation has a positive and significant effect on Job Satisfaction in employees, with the calculated value for the compensation variable (X1) being 6,794 and the sig value being 0.000 < 0.05. Motivation has a positive and significant effect on job satisfaction in employees, with the calculated value for the motivation variable (X2) being 3,481 and the sig value being 0.002 < 0.05. An adjusted R2 value of 0.651 or 65.1% was obtained. This shows that job satisfaction can be explained by 65.1% by compensation and motivation. While 34.9% of the Job Satisfaction variable was explained by variables outside the independent variable of this study.